Estimating HCV disease burden—volume 4 (editorial). (4th November 2017) - Dore, G.J.; Hatzakis, A.; Negro, F.; Waked, I.
Summary: Hepatitis C virus (HCV) is a major global public health issue, with an estimated 71 million people living with HCV infection and a rising burden of cirrhosis, hepatocellular carcinoma (HCC) and liver‐related mortality. The advent of interferon‐free, direct acting antiviral‐based (DAA) therapies, with short duration (8‐12 weeks), high efficacy, excellent tolerability and ease of delivery (once daily oral dosing), is one of the major advances in clinical medicine in recent decades, and provides the opportunity to address this growing global HCV burden. In May 2014, January 2015 and December 2015, three supplements were published in the Journal of Viral Hepatitis presenting data from 47 countries on the historical epidemiology of HCV, the current HCV‐related morbidity and mortality and potential strategies to manage the HCV disease burden in the future. The countries included in those manuscripts were from multiple regions including North and South America, Europe, Asia, the Middle East, Africa and Oceania. In this supplement, data from an additional 17 countries are presented, following a similar pattern as in the previous manuscripts. These countries represent a mixture of high‐, middle‐ and low‐income countries that hail from five geographical regions: Africa, Asia, Europe, Middle East and South America. Expert advisory panels were convened in each country to identify the best data sources to use and to review the assumptions and outputs from the model. In the countries considered in the current analyses, there is a wide variance in the availability of robust data.